Tuesday

July 29, 2014

July 29, 2014

Posted by **Molly** on Wednesday, February 19, 2014 at 7:57pm.

- algebra -
**Steve**, Thursday, February 20, 2014 at 12:15am2x-3y-3=0

x = 3(y+1)/2

y = 2/3 x - 1

y = 2/3 (x-3/2)

**Related Questions**

algebra - Simplify the following expression, and rewrite it in an equivalent ...

Algebra - Rewrite the equation 2x+4y+2=3y+5 in general form. A.2x+y-3=0 C.2x+y=3...

Math - Explain how to solve? Which equation below shows the equation y = – 1/4x...

math - hi, i need help with solving this equation for "y" 2x+3y=-2 2x+3y=-2 Get ...

bobpursly,.math - Ok, assume it equals zero. 2x + 3y -6=0 subtract 3y from each ...

Algebra 2 - If you were to use the substitution method to solve the following ...

correction of math - rewrite the equation 2x-3y= -6 as a function of x. My ...

math - 2x+3y=6 (solve for x) 2x+3y=6 Get unknown on one side and everything else...

algebra - write each equation in slope-intercept form. then graph the line ...

math - A linear system may have a unique solution, no solution, or infinitely ...